Student Performance Analysis System (SPAS) - Chew, Li Sa; Dayang Hanani, Abang Ibrahim; Emmy Dahliana, Hossain; Mohammad, Hossin (IEEE, 2015)
Almost every university have their own management system to manage the students' records. Currently, even though there is a student management system that manages the students' records in Universiti Malaysia Sarawak (UNIMAS), no permission is provided for lecturers to access the system. This is because the access permission is only to top management such as Deans and Deputy Deans of Undergraduate and Student Development due to its privacy setting. Thus, this project proposes a system named Student performance analysis system (SPAS) to keep track of students' result in the Faculty of Computer Science and Information Technology (FCSIT). The proposed system offer a predictive system that is able to predict the students' performance in course “TMC1013 System Analysis and Design”, which in turns assists the lecturers from Information System department to identify students that are predicted to have bad performance in course “TMC1013 System Analysis and Design”. The proposed system offers student performance prediction through the rules generated via data mining technique. The data mining technique used in this project is classification, which classifies the students based on students' grade.